The Presence of Serum TgAb Suggests Lower Risks for Glucose and Lipid Metabolic Disorders in Euthyroid General Population From a National Survey - Zhang, Jinjia; Gao, Yiyang; Li, Yongze; Teng, Di; Xue, Yuanming; Yan, Li; Yang, Jing; Yang, Lihui; Yao, Yongli; Ba, Jianming; Chen, Bing; Du, Jianling; et al. (Frontiers in Endocrinology, 2020)
Purpose: The expression of antibodies against thyroid peroxidase (TPOAb) and thyroglobulin (TgAb) are very common in the sera of patients with autoimmune thyroid diseases (AITD). The relationship between thyroid auto-antibodies and the occurrence of glucose and lipid metabolic disorders remains unclear. This study was performed to investigate the correlation between the presence of serum TPOAb/TgAb and those metabolic disorders in euthyroid general population. Methods: The data of this study was derived from the Thyroid Disease, Iodine status and Diabetes National epidemiological (TIDE) survey, a recent national survey. A total of 17964 subjects including 5802 males (4000 with TPOAb-TgAb- and 1802 with TPOAb+/TgAb+) and 12162 females (8000 with TPOAb-TgAb- and 4162 with TPOAb+/TgAb+) were enrolled in this study. The blood glucose and lipid levels were compared between individuals with TPOAb-TgAb- and those with TPOAb+TgAb-, TPOAb-TgAb+, TPOAb+TgAb+, respectively. Results: Both the fasting blood glucose (FBG) concentration and the proportion of individuals with impaired FBG (IFG) showed a decreased trend in TPOAb-TgAb+ males as compared with those TPOAb-TgAb- men. There were significantly lower FBG and higher HDL-C levels as well as tendencies to decreased incidences of IGT and hypertriglyceridemia in the TPOAb-TgAb+ females when compared with those TPOAb-TgAb- women. Binary logistic regression analysis further showed that serum TgAb single positivity in males was an independent protective factor for IFG with an OR of 0.688 (0.501-0.945). For females, serum TgAb single positivity was an independent protective factor for hypertriglyceridemia with an OR of 0.860 (0.749-0.988). Trend test showed that with the increase of serum TgAb level, there was a tendency of decrease in the prevalence of IFG among the men (P for trend=0.064) and that of hypertriglyceridemia in women (P for trend=0.047) who were all euthyroid. Conclusion: Serum TgAb single positivity may imply a reduced risk of IFG in euthyroid men and that of hypertriglyceridemia in euthyroid women. The mechanisms related to these interesting phenomena await further investigation.